The Influence of Investment Decisions and Funding Decisions on Company Value (Study of Transportation and Logistics Companies on the IDX) - Lorenza, Imah Maulana; Hidayat, Rendra Arief (Jurnal Wacana Ekonomi, 2024)
There are many developing countries in Southeast Asia and Indonesia is one of them that is highlighted by the world. With the transportation and logistics industry which has become one of the bloodstreams of the process of providing services and facilities to the population of this country. The existence of the transportation and logistics sector plays an important role in improving people's quality of life. If a transportation and logistics company wants to develop its business further, it needs external financial assistance, including investors. Investors are parties who are willing to provide capital assistance by investing their capital in the company. The theory used in this research is based on the use of signal theory. The method of this research uses quantitative methods and uses secondary evidence taken via the official IDX website This research aims to determine the effect of investment decisions and funding decisions on the value of a company using dividend policy (distribution of share profits) as a moderating variable. The result of this observation is that decisions regarding investment and decisions regarding funding have a positive effect on the value of transportation and logistics companies in Indonesia. Dividend policy has negative results and cannot strengthen the effect of decisions regarding investment and decisions regarding funding on company value. Keywords : Transportation, Logistics, Investment, Funding, Dividends.